2013
DOI: 10.1161/circep.112.974220
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Mechanisms of Action of Novel Na V 1.5 Channel Mutations Associated With Brugada Syndrome

Abstract: Background— Brugada syndrome is a heterogeneous heart rhythm disorder characterized by an atypical right bundle block pattern with ST-segment elevation and T-wave inversion in the right precordial leads. Loss-of-function mutations in SCN5A encoding the cardiac sodium channel Na V 1.5 are associated with Brugada syndrome. We found novel mutations in SCN5A in 2 different families diagnosed with Brugada … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 21 publications
(21 reference statements)
1
21
0
2
Order By: Relevance
“…The abnormal BrS AP profile was explained by a reduction in I Na and upstroke velocity, a phenotype consistent with the loss of hNa v 1.5 function predicted by SCN5A variants utilizing heterologous expression models (29,3335). The reduction in I Na is similar to results by Davis et al who studied human iPSC-CMs from subjects with an overlap syndrome with Type 3 Long QT and BrS features and demonstrated reduced I Na current density and upstroke velocity (36).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The abnormal BrS AP profile was explained by a reduction in I Na and upstroke velocity, a phenotype consistent with the loss of hNa v 1.5 function predicted by SCN5A variants utilizing heterologous expression models (29,3335). The reduction in I Na is similar to results by Davis et al who studied human iPSC-CMs from subjects with an overlap syndrome with Type 3 Long QT and BrS features and demonstrated reduced I Na current density and upstroke velocity (36).…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, the patient had a family history of sudden death in two paternal uncles and a female cousin. Genetic testing revealed a double missense mutation (R620H and R811H) in SCN5A gene domain IIS4, with R811H known to be critical in voltage-dependent gating (Figure 1C, Supplemental Figure 1A, and Supplemental Table 2) (29). …”
Section: Resultsmentioning
confidence: 99%
“…We found that the density of Na + currrent was reduced to ∼60% of the WT Na + current density, and the voltage dependence of inactivation was also shifted towards negative voltages compared to the WT channel. Some research showed that when co-expressing trafficking-deficient BrS SCN5A mutations with WT Na v 1.5 channel (0.5:0.5 in ratio) in heterologous expression systems, it is observed that the Na + current was reduced by about 50% compared to the Na + current produced by expressing only WT Na v 1.5 channel [33][34][35]. Such reduction of Na + current is due to the haploinsufficiency of WT Na v 1.5 channel.…”
Section: Discussionmentioning
confidence: 99%
“…31 Mokimoto et al studied 93 patients with BrS and 102 healthy control subjects during recovery phase from treadmill exercise testing. 32 Twentytwo patients had previous documented VF, 35 had history of syncope alone and 36 were asymptomatic among BrS patients.…”
Section: Augmented St Elevation During Recovery From Exercise In Patimentioning
confidence: 99%